Delivery of VP1 siRNA to inhibit the EV71 virus using functionalized silver nanoparticles through ROS-mediated signaling pathways. Issue 3 (5th January 2017) - Li, Yinghua; Lin, Zhengfang; Xu, Tiantian; Wang, Changbing; Zhao, Mingqi; Xiao, Misi; Wang, Hanzhong; Deng, Ning; Zhu, Bing
Abstract : Enterovirus 71 (EV71) is the primary causative agent of hand, foot, and mouth disease (HFMD). Abstract : Enterovirus 71 (EV71) is the primary causative agent of hand, foot, and mouth disease (HFMD). There is no effective drug therapy for EV71 at present. Small interfering RNA (siRNA), as a new therapeutic modality, provides a promising antiviral treatment, but it is unable to cross cell membranes. To overcome this limitation, nanotechnology has been proposed to mediate siRNA transfection. The antiviral activity of silver nanoparticles (AgNPs) has attracted increasing attention in recent years and can be employed in biomedical interventions. In this study, a simple method to prepare surface decorated AgNPs using polyethylenimine (PEI) and antiviral siRNA has been demonstrated. The development of AgNPs and PEI co-delivery of siRNA was designed to be antiviral. MTT assays and TEM images showed that PEI and siRNA-modified AgNPs (Ag@PEI@siRNA) have remarkable inhibition against EV71 infection and less toxicity to Vero cells. The mechanistic investigations revealed that Ag@PEI@siRNA could block EV71 from infecting host cells and prevent DNA fragmentation, chromatin condensation and activation of caspase-3. Ag@PEI@siRNA effectively inhibited the accumulation of reactive oxygen species (ROS) by the EV71 virus and activation of AKT and p53. Taken together, this study demonstrates that Ag@PEI@siRNA is a novel promising efficient virucide for EV71.